Epidemiology of malocclusion in children and adolescents: a critic review - CARVALHO,Fábio Silva de (2014)
OBJECTIVES: The aim of this literature review about malocclusion was to identify epidemiologic instruments which are being used in Public Health, as well as to bring information regarding the occlusal alterations more prevalent in children and adolescents. METHODS: Information presented in previous studies was reviewed, in articles published in period 1997-2007, considering the production registered in the following databases: Latin American and Caribbean Health Sciences, Scientific Electronic Library Online, International Database for Medical Literature and Brazilian Dentistry Bibliography. RESULTS: The total of 191 identified references, 170 had been eliminated after the implementation of the exclusion criteria and 21 articles met the proposed inclusion criteria and had served of base for this work. The use of different criteria made difficult the comparison of studies in literature and did not offer parameters that can guide the scientific evidences. CONCLUSION: The most used epidemiologic indices were Dental Aesthetic Index and Index of Orthodontic Treatment Need and it was observed predominance of open bite in the deciduous dentition and crowding in the mixed and permanent dentitions.